Long-acting antipsychotic treatments: focus on women with schizophrenia - Sofia Brissos; Vicent Balanzá-Martínez (SAGE Publishing, 2024)
Effective management of schizophrenia (SZ) requires long-term treatment with antipsychotics (APs) to prevent clinical relapse, attain remission and improve patients' personal and social functioning, and quality of life. Although APs remain the cornerstone treatment for patients with SZ, despite their potential benefits, long-acting injectable APs (LAI-APs) remain underused, most notably in women with SZ. The efficacy and tolerability of APs differ significantly between men and women, and some of these differences are more noticeable depending on the patient's age and the stage of the disorder. Although sex differences may influence treatment outcomes in SZ, their pertinence has been insufficiently addressed, especially regarding the use of LAI-APs. Some biological and social experiences, such as pregnancy, lactation, contraception and menopause, are specific to women, but these remain under-researched issues. Implications of this disorder in parenting are also of special pertinence regarding women; therefore, taking sex differences into account when treating SZ patients is now recommended, and improving personalized approaches has been proposed as a priority in the management of psychosis. In this narrative, critical review, we address some aspects specific to sex and their implications for the clinical management of women with SZ, with a special focus on the potential role of LAI-AP treatments.